PENGHUNI GUA KIDANG: PENJELAJAH TANGGUH DI KAWASAN KARST BLORA - Indah Asikin Nurani (Balai Arkeologi Yogyakarta, 2011)
Prehistoric period of human life is relying on the availability of the potential of the surrounding natural environment in maintaining life. Prehistoric people will look for areas that provide the necessities of life either food source or sources of raw material to equipment. Kidang cave is one of prehistoric cave dwelling occupied intensively in the long term. Archaeological evidence, and traces ecofact fireplace and the grave gave an overview of how human beings to survive that period. This paper will discuss how patterns of human life of Kidang cave adapting to the natural environment on the aspects of diet, technology, and mobility of residents in search of food sources and sources of raw materials for everyday equipment.